A novel TNFRSF1A splice mutation associated with increased nuclear factor κappaB (NF-κB) transcription factor activation in patients with tumour necrosis factor receptor associated periodic syndrome (TRAPS). Issue 11 (17th December 2007) - Churchman, S M; Church, L D; Savic, S; Coulthard, L R; Hayward, B; Nedjai, B; Turner, M D; Mathews, R J; Baguley, E; Hitman, G A; Gooi, H C; Wood, P M D; et al.
Abstract : Objective: To characterise and investigate the functional consequences of a novel TNFRSF1A splice site mutation causing tumour necrosis factor receptor associated periodic syndrome (TRAPS) in a 16-year-old male patient and his mother. Methods: Mutational DNA screening was performed in the patient and his mother. Western blotting was used to analyse protein expression levels of TNFR1. A multiplex bead immunoassay was used to quantify serum levels of range of cytokines, and an ELISA-based transcription factor assay to measure nuclear factor (NF)-κB transactivation. Serum levels of soluble TNFR1 (sTNFR1) were measured by ELISA and fluorescence-activated cell sorting (FACS) analysis used to measure monocyte TNFR1 cell surface expression. Results: A novel mutation, c.472+1G>A (C158delinsYERSSPEAKPSPHPRG), involving a splice site in intron 4 of TNFRSF1A, was found in the proband and affected mother leading to a 45 nucleotide insertion of intronic DNA into the mRNA, resulting in an in-frame insertion of 15 amino acids in the mature TNFR1 protein and a deletion of a cysteine residue C129 (158) in cysteine rich domain (CRD)3. The patients had reduced serum sTNFR1 and surface expression levels of TNFR1, with marked increases in pro- and anti-inflammatory cytokine. Their peripheral blood mononuclear cells (PBMC) had increased basal NF-κB activation compared with healthy controls and also had increased p50 nuclear expression following tumour necrosis factor (TNF) stimulation compared with PBMC from healthy controls, as well as T50M (T79M) and C88R (C117R) patients with TRAPS and patients with rheumatoid arthritis (RA). Conclusion: A novel, TRAPS causing, TNFRSF1A splice site mutation is associated with decreased sTNFR1 levels, cell surface and whole cell extract expression and increased NF-κB transcription factor activation.